2008
DOI: 10.1111/j.1574-6968.2008.01090.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo proteome analysis of Xanthomonas campestris pv. campestris in the interaction with the host plant Brassica oleracea

Abstract: The genus Xanthomonas is composed of several species that cause severe crop losses around the world. In Latin America, one of the most relevant species is Xanthomonas campestris pv. campestris, which is responsible for black rot in cruciferous plants. This pathogen causes yield losses in several cultures, including cabbage, cauliflower and broccoli. Although the complete structural genome of X. campestris pv. campestris has been elucidated, little is known about the protein expression of this pathogen in close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 35 publications
(39 reference statements)
1
33
0
Order By: Relevance
“…6 Infection of Arabidopsis suspension cells with Pseudomonas syringae resulted in the secretion collection of 45 Arabidopsis secreted proteins, 7 and similar sized collections of proteins were obtained from Xanthamonas campestris infection of Brassica oleracea although in this case most of the proteins identified were of bacterial origin. 8 The proteome of tomato fruits ( Lycopersicon esculentum ) infected with TMV identified 16 proteins. including several pathogenesis-related (PR) proteins and antioxidant enzymes found that may be part of the plant resistance response to viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…6 Infection of Arabidopsis suspension cells with Pseudomonas syringae resulted in the secretion collection of 45 Arabidopsis secreted proteins, 7 and similar sized collections of proteins were obtained from Xanthamonas campestris infection of Brassica oleracea although in this case most of the proteins identified were of bacterial origin. 8 The proteome of tomato fruits ( Lycopersicon esculentum ) infected with TMV identified 16 proteins. including several pathogenesis-related (PR) proteins and antioxidant enzymes found that may be part of the plant resistance response to viral infection.…”
Section: Introductionmentioning
confidence: 99%
“…campestris in association with B. oleracea and Pseudomonas savastanoi pv. savastanoi resulted in comprehensive expression analysis including stress and metabolic proteins (Andrade et al, 2008; Campos et al, 2009). Increased levels of proteins involved in xanthan biosynthesis, stress response, and the metabolism were induced in X. campestris in planta conditions compared with in vitro grown cells (Andrade et al, 2008).…”
Section: Proteome Analyses Of Plant Associated Bacteriamentioning
confidence: 99%
“…savastanoi resulted in comprehensive expression analysis including stress and metabolic proteins (Andrade et al, 2008; Campos et al, 2009). Increased levels of proteins involved in xanthan biosynthesis, stress response, and the metabolism were induced in X. campestris in planta conditions compared with in vitro grown cells (Andrade et al, 2008). Chaperonin is reported to be involved in stress responses and EF, which acts as an important PTI in the plants, is the key component of the translational machinery of bacteria.…”
Section: Proteome Analyses Of Plant Associated Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Using this protocol and the corresponding proteomics approaches, Andrade et al . () analysed the in vivo proteome of X. campestris pv. campestris in different cultivars of infected Brassica oleracea .…”
Section: Introductionmentioning
confidence: 97%